Dependence of the Passive Force Fp From the Revolutions, back Engagement of Cutting Edge Ae, Working Engagement of the Cutting Edge Ap During Milling - Javorek, Lubomir (International Journal of Engineering and Management Sciences, 2019)
In this contribution is analysed the force component of final force (passive force) by peripheral milling operation. Therefore, the main parameters that had influence to independent variable were revolutions, back engagement of a cutting edge ae, working engagement of the cutting edge ap. The article deals with the issue of milling in material AlMgSi0.5 (aluminium alloy). Specifically evaluates the force component with respect to change of revolutions (4000/min., 5000/min., 6000/min.), working engagement of the cutting edge ap (1 mm, 2 mm, 3 mm) and back engagement of a cutting edge ae (5 mm, 10 mm, 15 mm). The Alfaflex process fluid with 7% concentration was supplied in an amount of about cca 10 l/min.